Accuracy of endoscopic ultrasound in rectal cancer and its use in transanal endoscopic microsurgery - Gao, Yuan; Hu, Ji-Lin; Zhang, Xian-Xiang; Zhang, Mao-Shen; Zheng, Xue-Feng; Liu, Shi-Song; Lu, Yun (Minimally invasive therapy and allied technologies, 2020)
Introduction: This study evaluated the accuracy of endoscopic ultrasound (EUS) for preoperative staging of rectal cancer and guiding the treatment of transanal endoscopic microsurgery (TEM) in early rectal cancer. Material and methods: One-hundred-twenty-six patients with rectal cancer were staged preoperatively using EUS and the results were compared with postoperative histopathology results. Radical surgeries, including low anterior resection (LAR), abdominal-perineal resection (APR) and Hartmann surgeries, were performed on patients with advanced rectal cancers, and TEM was performed on patients with stage T1. The Kappa statistic was used to determine agreement between EUS-based staging and pathology staging. Results: The overall accuracies of EUS for T and N stage were 90.8% (Kappa = 0.709) and 76.7% (Kappa = 0.419), respectively. The accuracies of EUS for uT1, uT2, uT3, and uT4 stages were 96.8%, 92.1%, 84.1%, and 88.9%, respectively, and for uN0, uN1, and uN2 stages, they were 71.9%, 64.9%, and 93.0%, respectively. Twelve patients underwent TEM and received confirmed pathology results of early rectal cancer. After postoperative follow-up, there were no local recurrences or distant metastases. Conclusion: EUS is a good and comparable technique for postoperative staging of rectal cancer. Moreover, EUS is used as indicator for preoperative staging and tumor assessment strategy when considering TEM.